SAT0610-HPR COHERENT REHABILITATION – EXPERIENCES OF PEOPLE WITH INFLAMMATORY ARTHRITIS. (2nd June 2020) - Feddersen, H.; Soendergaard, J.; Schmidt, B. M.; Andersen, L.; Primdahl, J.
Abstract : Background: 20-40% of patients with inflammatory arthritis (IA) do not tolerate or do not have sufficient effect of the medication and experience considerable problems in their everyday lives. For these patients multidisciplinary rehabilitation and coherence in healthcare are of utmost importance (1). However, only little is known about coherence in healthcare among patients with inflammatory arthritis Objectives: To explore how persons with IA experience coherence in their rehabilitation pathways Methods: Semi-structured individual interviews with 11 persons with IA who had experience with rehabilitation across primary and secondary health care. Interviews were conducted in the patients' home before admission to an inpatient rehabilitation stay, during the admission and 2-3 weeks and 4-6 months after discharge. In addition, participant observations and informal interviews were performed during admission. The analysis involved case descriptions (2) and interpretation in a thematic analysis (3). Results: The analysis derived a main theme "a person centered approach", representing the importance for the person to meet professionals who listen and acknowledge the persons own views rather than focusing on the "system", regulations and standards. In addition, 4 sub-themes were identified: 1) "empowerment and disempowerment", covering how most patients want to be in control and take action but they may lack the energy and ability to express their needs and thus give up; 2) "Lack of communication and coordination", involving processes between the staff in the same department, between departments or sectors. Patients feel forced to take on coordinating tasks themselves, which they do not feel qualified to perform; 3) "Interventions meant as help may be felt as restrictions", which encompass i.e. free physical therapy delivered at times not appropriate for the patient and types of support which can lead to a feeling of social control, and finally, 4) "The system is difficult to get through". Information about possible support are provided at random and some ask for a coordinating person. Conclusion: Facilitators for coherent pathways among people with IA encompass dedicated professionals working with a person-centered approach aiming to empower people. This encompass to provide relevant knowledge and enable the person to ask for the right type of help. A coordinator may facilitate coherence. References: [1]Aiello M, Mellor JD. Integrating health and care in the 21st century workforce. Journal of Integrated Care. 2019;27(2):100-10. [2]Breimo JP. Bundet av bistand. En institusjonell etnografi om organisering av rehabiliteringsprosesser [Captured by Care. An Institutional Ethnography on organizing of Rehabilitation Processes]: Universitetet i Nordland; 2012. [3]Braun V, Clarke V, Hayfield N, Terry G. Thematic Analysis. In: Liamputtong P, editor. Handbook of Research Methods in Health Social Sciences. Singapore: Springer; 2019. Acknowledgments: Funding from Region of Southern Denmark, Hans Christensens memorial foundation and Knud and Edith Eriksens memorial foundation Disclosure of Interests: Helle Feddersen: None declared, Jens Soendergaard: None declared, Bettina Munksgaard Schmidt: None declared, Lena Andersen: None declared, Jette Primdahl Speakers bureau: BMS and Pfizer